2017
DOI: 10.1038/ncomms15713
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic climate change has altered primary productivity in Lake Superior

Abstract: Anthropogenic climate change has the potential to alter many facets of Earth's freshwater resources, especially lacustrine ecosystems. The effects of anthropogenic changes in Lake Superior, which is Earth's largest freshwater lake by area, are not well documented (spatially or temporally) and predicted future states in response to climate change vary. Here we show that Lake Superior experienced a slow, steady increase in production throughout the Holocene using (paleo)productivity proxies in lacustrine sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(58 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…Many previous studies have shown that the increases in phytoplankton primary production and algal blooms are associated with climate warming (Joehnk et al, ; Michalak et al, ; O'Beirne et al, ; Paerl & Huisman, ). Experiments, field observations and remote sensing monitoring in Lake Taihu confirmed that climate warming has promoted an advance of the date of the initial algal bloom, prolonged the growing season and the yearly duration, enlarged the area of algal blooms, and delayed the date of the last algal blooms (Deng et al, ; Duan et al, ; Ma et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies have shown that the increases in phytoplankton primary production and algal blooms are associated with climate warming (Joehnk et al, ; Michalak et al, ; O'Beirne et al, ; Paerl & Huisman, ). Experiments, field observations and remote sensing monitoring in Lake Taihu confirmed that climate warming has promoted an advance of the date of the initial algal bloom, prolonged the growing season and the yearly duration, enlarged the area of algal blooms, and delayed the date of the last algal blooms (Deng et al, ; Duan et al, ; Ma et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies that have used either direct observations and experimental evidences or theoretical and model inferences have shown that anthropogenic global change is predicted to increasingly affect lake environments and ecosystems (Cohen et al, ; Farmer et al, ; O'Beirne et al, ; Pace et al, ; Smol et al, ). However, long‐term observations are more difficult to obtain in lake ecosystems than in terrestrial ecosystems, and presently available observation periods are very limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct impact of climate on lakes is climate-driven modulation of lake surface water temperature (LSWT), with potential consequences for a broad range of physical and ecological factors (De Stasio et al, 1996). Rising LSWTs can influence metabolic processes (Kraemer et al, 2017), enhance greenhouse gas emissions (Yvon-Durocher et al, 2014) and modify the key processes of vertical mixing and stratification leading to an increased occurrence of cyanobacterial blooms (Jöhnk et al, 2008), deepwater hypoxia (Jankowski et al, 2006;North et al, 2014) and changes in lake productivity (O'Beirne et al, 2017;O'Reilly et al, 2003). A detailed understanding of LSWT warming, and the factors that control it, is therefore essential for climate change impact studies.…”
Section: Introductionmentioning
confidence: 99%
“…By modifying the key processes of mixing and stratification (Peeters et al 2002;Perroud and Goyette 2010;Stainsby et al 2011), climate-driven modulation of surface heat fluxes can alter key aspects of lake ecosystems, such as an increased occurrence of toxic cyanobacterial blooms (Jöhnk et al 2008), deep-water hypoxia (Jankowski et al 2006;North et al 2014), and changes in lake productivity (Verburg et al 2003;O'Beirne et al 2017). Evaporative heat fluxes also alter lake levels (Gronewold and Stow 2014), with consequences for water security and supply (Brookes et al 2014) and, in turn, water management strategies (Vörösmarty et al 2000;Immerzeel et al 2010;Vörösmarty et al 2010).…”
mentioning
confidence: 99%